Dynamics of Memory B-Cell Populations in Blood, Lymph Nodes, and Bone Marrow during Antiretroviral Therapy and Envelope Boosting in Simian Immunodeficiency Virus SIVmac251-Infected Rhesus Macaques - Demberg, Thorsten (American Society for Microbiology, 2012)
Human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) infection causes B-cell dysregulation and the loss of memory B cells in peripheral blood mononuclear cells (PBMC). These effects are not completely reversed by antiretroviral treatment (ART). To further elucidate B-cell changes during chronic SIV infection and treatment, we investigated memory B-cell subpopulations and plasma cells/plasmablasts (PC/PB) in blood, bone marrow, and lymph nodes of rhesus macaques during ART and upon release from ART. Macaques previously immunized with SIV recombinants and the gp120 protein were included to assess the effects of prior vaccination. ART was administered for 11 weeks, with or without gp120 boosting at week 9. Naïve and resting, activated, and tissue-like memory B cells and PC/PB were evaluated by flow cytometry. Antibody-secreting cells (ASC) and serum antibody titers were assessed. No lasting changes in B-cell memory subpopulations occurred in bone marrow and lymph nodes, but significant decreases in numbers of activated memory B cells and increases in numbers of tissue-like memory B cells persisted in PBMC. Macaque PC/PB were found to be either CD27(+) or CD27(−) and therefore were defined as CD19(+) CD38(hi) CD138(+). The numbers of these PC/PB were transiently increased in both PBMC and bone marrow following gp120 boosting of the unvaccinated and vaccinated macaque groups. Similarly, ASC numbers in PBMC and bone marrow of the two macaque groups also transiently increased following envelope boosting. Nevertheless, serum binding titers against SIVgp120 remained unchanged. Thus, even during chronic SIV infection, B cells respond to antigen, but long-term memory does not develop, perhaps due to germinal center destruction. Earlier and/or prolonged treatment to allow the generation of virus-specific long-term memory B cells should benefit ART/therapeutic vaccination regimens.